2013
DOI: 10.2298/vsp110224042s
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric assessment of maxillary length in Serbian children with skeletal class III

Abstract: The children with skeletal class III have significantly shorter maxilla than those with skeletal class I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
3
1
1
Order By: Relevance
“…24 With regard to norms to identify relative maxillary hypoplasia, previous authors reported a normal maxillary complex to anterior cranial base ratio of 65 6 3%. 18 However, that sample consisted of Caucasian children and may not be comparable to the present results as the anterior cranial base is shorter in Asians compared to Caucasians. 27 Furthermore, other authors reported no differences in the maxillary complex to anterior cranial base ratio between Class III subjects (127.8 6 4.1%) and controls (130.5 6 4.5%).…”
Section: Maxillary Anteroposterior Lengthcontrasting
confidence: 78%
See 3 more Smart Citations
“…24 With regard to norms to identify relative maxillary hypoplasia, previous authors reported a normal maxillary complex to anterior cranial base ratio of 65 6 3%. 18 However, that sample consisted of Caucasian children and may not be comparable to the present results as the anterior cranial base is shorter in Asians compared to Caucasians. 27 Furthermore, other authors reported no differences in the maxillary complex to anterior cranial base ratio between Class III subjects (127.8 6 4.1%) and controls (130.5 6 4.5%).…”
Section: Maxillary Anteroposterior Lengthcontrasting
confidence: 78%
“…Ten skulls not included in the final study were included in a pilot study, showing a standard deviation (SD) of 5.7 mm for ans-pns and 6% for ans-pns/SN, which were the primary parameters for each criterion, respectively. Setting a clinically significant difference of 5.0 mm 11,[17][18][19][20] and 5% 15,18 between the two groups, respectively, a significance level a ¼ 0.05, and a power b ¼ 90%, the required sample size was 30 skulls for each group.…”
Section: Sample Size Calculationmentioning
confidence: 99%
See 2 more Smart Citations
“…Apsolutne vrednosti antropometrijskih vrednosti dečaka su komparirani sa rezultatima devojčica iste starosne grupe [6,7]. Indeks kraniofacijalne varijabilnosti (CVI) kreiran je za grupu ispitanika serijom antropometrijskog merenja lica i lobanje za svaku uzrasnu grupu za oba pola, kako je i prikazano tabelama.Ovaj indeks je mera varijacije koja iskazuje odstupanje od pojedinačne vrednosti obeležja od srednje vrednostiu broju standardnih devijacija [6,7,8,9,10]. …”
unclassified